TAX PLANNING, PROFITABILITY, AND GOOD CORPORATE GOVERNANCE ON EARNINGS MANAGEMENT WITH COMPANY SIZE AS A MODERATING VARIABLE - Aisyah Firdaus, Nisrina; Maryanti, Eny (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2024)
There are factors that are considered to influence earnings management, namely tax planning, profitability and good corporate governance. In this research, the company size variable will be added as a moderating variable to prove its influence on these three factors. The population in this research are Consumer Sector listed on the Indonesia Stock Exchange in 2019-2022 with a total population of 76 companies. The sampling technique uses purposive sampling by selecting several criteria. This research uses IBM SPSS Version 26 software with multiple linear regression analysis or MRA. The results showed that tax planning has no effect on earnings management, but profitability and good corporate governance negatively affect earnings management. Meanwhile, company size is unable to moderate the effect of tax planning on earnings management but company size is able to weaken the effect of good corporate governance on earnings management. Companies are expected to be able to prevent and reduce opportunistic actions and continuously evaluate all policies for the future.